Perawatan Bayi Baru Lahir dengan Pendekatan Model Mother-Baby Care (M-BC) Sebagai Inovasi dalam Upaya Memandirikan Ibu Postpartum: Newborn Care with a Model Approach Mother-Baby Care (M-BC) as an Innovation in Efforts Independence of Postpartum Mothers - Vetty Priscilla (Fakultas Keperawatan Universitas Andalas, 2013)
Newborn care is very important to do after the baby was born and is useful for both mother and baby. Rapid resumption of maternal organs that undergo changes during pregnancy is one of the advantages besides make warm relationship between mother and baby. The purpose of this study was to make postpartum mothers to be more independent in order to care of newborn by using model of Mother-Baby Care (M-BC). This study was using a qualitative design with a grounded theory approach. The sample was 10 postpartum in Dr MJamil hospital Padang. The result is an innovation model of Mother-Baby Care (M-BC) in newborn care. It is recommended especially for health workers to use this model as one of the innovations in the newborn care.